Adenomyosis and endometriosis: re-visiting their association and further insights into the mechanisms of auto-traumatisation : an MRI study - Leyendecker, Gerhard; Huppert, Peter E.; Mall, Gerhard (Archives of gynecology and obstetrics, 2015)
Purpose: in a series of publications, we had developed the concept that uterine adenomyosis and pelvic endometriosis as well as endometriotic lesions at distant sites of the body share a common pathophysiology with endometriosis constituting a secondary phenomenon. Uterine auto-traumatization and the initiation of the mechanism of tissue injury and repair (TIAR) were considered the primary events in the disease process. The present MRI study was undertaken (1) to corroborate this concept by re-visiting, in view of discrepant results in the literature, the association of adenomyosis with endometriosis and (2) to extend our views concerning the mechanisms of uterine auto-traumatization.Patients and methodsMRI was performed in 143 women attending our center, in whom, on the basis of transvaginal sonography (TVS) and historical data, such as documented endometriosis and dysmenorrhea of various degrees of severity, the presence of uterine adenomyosis was suspected. In addition to the measurement of the diameter of junctional zone (JZ) of the anterior and posterior walls in the mid-sagittal plane, the diagnosis of adenomyosis was based on visualization, in that all planes were analyzed with scrutiny. By this method of “visualization” all transient enlargement of the JZ, such as peristaltic waves of the archimyometrium and sporadic neometral contractions that might mimic adenomyotic lesions could be excluded. At the same time, this method allowed to lower the limit of detection in terms of thickness of the JZ for assured diagnosis of adenomyosis. Furthermore, the localizations of the individual lesions, their shapes and patterns were described.ResultsWith the method of ‘visualization’, the diagnosis of uterine adenomyosis could be verified in 127 of the 143 patients studied. The prevalence of endometriosis in adenomyosis was 80.6 % and the prevalence of adenomyosis in endometriosis was 91.1 %. As concluded from their localization within the uterine wall, the adenomyotic lesions predominantly developed in the median region of the upper two-thirds of the uterine wall. Cystic cornual angle adenomyosis was a distinct phenomenon that was only observed in patients suffering from extreme primary dysmenorrhea. Aside from this, the majority of the patients complained of primary dysmenorrhea (80 %). On the basis of these findings and the fact that particularly extreme primary dysmenorrhea is associated with high intrauterine pressure, menstrual ‘archimetral compression by neometral contraction’ has to be considered as an important cause of uterine auto-traumatization in addition to uterine peristalsis and hyperperistalsis. Both mechanical functions of the non-pregnant uterus exert their strongest power in the upper region of the uterus, which is compatible with the predominant localization of the adenomyotic lesions.ConclusionsThe data confirm our previous results of a high association of adenomyosis with endometriosis and vice versa. Our view of the mechanism of uterine auto-traumatization by mechanical functions of the non-pregnant uterus has to be extended, in that ‘archimetral compression by neometral contractions’ could be realized as the predominant cause of mechanical strain to the non-pregnant uterus. The data of this study confirm our concept of the etiology and pathophysiology of adenomyosis and endometriosis in that the process of chronic proliferation and inflammation is induced at the level of the archimetra by chronic uterine auto-traumatization. Furthermore, with respect to the diagnosis of uterine adenomyosis (and consequently endometriosis) this study shows a high degree of accordance between the findings in real-time TVS and MRI.